SEMIOTIKA PIERCE PADA FILM DOKUMENTER ‘SEXY KILLERS’ - Niluh Wiwik Eka Putri (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
In YouTube, Watchdoc Image's viral account on social media has generated much speculation for the public. Particularly in politics, because this documentary was released a few days before the simultaneous general elections in Indonesia on April 17, 2019. Overall, the sign in the 7 scenes above uses a brighter background color and indicates sadness when viewing footage in the video documentary film sexy killers. Some of the signs in the scene are explosions in the ground, the ocean, murky water, the Coal Mine Project, the sound of houses collapsing, all-white clothing and tombstones, Basarnas Clothing. From object classification, i.e. icons, indexes and symbols, we can find out the meaning of the relationship between signs and objects. The icons that appear in each scene picture display a model that is closely related to the coal mining project. Some of the objects visible include coal, coal hauling barges, a man bathing in muddy water, the face of Kertha Buana Village, houses that have collapsed due to coal mining activities and damaged roads, demo residents, and the Basarnas team. Interpretant or assumptions from the author Seen from the form of parody supported by digital image processing techniques, namely